(untitled) (Scientific journal of the Fergana State University, 2023)
This article is devoted to the study of the influence of the rhyme level on the poetics of Alisher Navoi’s work "Nazm ul-javahir". In it, based on the structural method, the types of the rhyme of this work are mujarrad, murdaf, muqayyad and muassas rhymes according to the content of the poem before the raviy; the types of muqayyad and mutlaq rhymes according to the content of the poem after the raviy have been extensively researched and it has been revealed that the rhymes used in the rubaiys of “Nazm ul-javahir” ensure the perfection of the poetics of the work.